Impact of ADCY9 Genotype on Response to Anacetrapib. Issue 11 (10th September 2019) - Hopewell, Jemma C.; Ibrahim, Maysson; Hill, Michael; Shaw, Peter M.; Braunwald, Eugene; Blaustein, Robert O.; Bowman, Louise; Landray, Martin J.; Sabatine, Marc S.; Collins, Rory
Abstract : Background: Exploratory analyses of previous randomized trials generated a hypothesis that the clinical response to cholesteryl ester transfer protein (CETP) inhibitor therapy differs by ADCY9 genotype, prompting the ongoing dal-GenE trial in individuals with a particular genetic profile. The randomized placebo-controlled REVEAL trial (Randomized Evaluation of the Effects of Anacetrapib through Lipid-Modification) demonstrated the clinical efficacy of the CETP inhibitor anacetrapib among patients with preexisting atherosclerotic vascular disease. In the present study, we examined the impact of ADCY9 genotype on response to anacetrapib in the REVEAL trial. Methods: Individuals with stable atherosclerotic vascular disease who were treated with intensive atorvastatin therapy received either anacetrapib 100 mg daily or matching placebo. Cox proportional hazards models, adjusted for the first 5 principal components of ancestry, were used to estimate the effects of allocation to anacetrapib on major vascular events (a composite of coronary death, myocardial infarction, coronary revascularization, or presumed ischemic stroke) and the interaction with ADCY9 rs1967309 genotype. Results: Among 19 210 genotyped individuals of European ancestry, 2504 (13.0%) had a first major vascular event during 4 years median follow-up: 1216 (12.6%) among anacetrapib-allocated participants and 1288 (13.4%) among placebo-allocated participants. Proportional reductions in the risk of major vascular events with anacetrapib did not differ significantly by ADCY9 genotype: hazard ratio (HR) = 0.92 (95% CI, 0.81–1.05) for GG; HR = 0.94 (95% CI, 0.84–1.06) for AG; and HR = 0.93 (95% CI, 0.76–1.13) for AA genotype carriers, respectively; genotypic P for interaction = 0.96. Furthermore, there were no associations between ADCY9 genotype and the proportional reductions in the separate components of major vascular events or meaningful differences in lipid response to anacetrapib. Conclusions: The REVEAL trial is the single largest study to date evaluating the ADCY9 pharmacogenetic interaction. It provides no support for the hypothesis that ADCY9 genotype is materially relevant to the clinical effects of the CETP inhibitor anacetrapib. The ongoing dal-GenE study will provide direct evidence as to whether there is any specific pharmacogenetic interaction with dalcetrapib. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01252953. URL: http://www.isrctn.com . Unique identifier: ISRCTN48678192. URL: https://www.clinicaltrialsregister.eu . Unique identifier: 2010-023467-18. Abstract : Supplemental Digital Content is available in the text.